Molecular architecture of the endocytic TPLATE complex - Yperman, Klaas; Wang, Jie; Eeckhout, Dominique; Winkler, Joanna; Vu, Lam Dai; Vandorpe, Michael; Grones, Peter; Mylle, Evelien; Kraus, Michael; Merceron, Romain; Nolf, Jonah; Mor, Eliana; et al. (Science advances, 2021)
Eukaryotic cells rely on endocytosis to regulate their plasma membrane proteome and lipidome. Most eukaryotic groups, except fungi and animals, have retained the evolutionary ancient TSET complex as an endocytic regulator. Unlike other coatomer complexes, structural insight into TSET is lacking. Here, we reveal the molecular architecture of plant TSET [TPLATE complex (TPC)] using an integrative structural approach. We identify crucial roles for specific TSET subunits in complex assembly and membrane interaction. Our data therefore generate fresh insight into the differences between the hexameric TSET in Dictyostelium and the octameric TPC in plants. Structural elucidation of this ancient adaptor complex represents the missing piece in the coatomer puzzle and vastly advances our functional as well as evolutionary insight into the process of endocytosis.